Does Location of Rotation Center in Artificial Disc Affect Cervical Biomechanics?. Issue 8 (15th April 2015) - Mo, Zhongjun; Zhao, Yanbin; Du, Chengfei; Sun, Yu; Zhang, Ming; Fan, Yubo
<x xml:space="preserve">Abstract</x> Study Design. A 3-dimensional finite element investigation. Objective. To compare the biomechanical performances of different rotation centers (RCs) in the prevalent artificial cervical discs. Summary of Background Data. Various configurations are applied in artificial discs. Design parameters may influence the biomechanics of implanted spine. The RC is a primary variation in the popular artificial discs. Methods. Implantation of 5 prostheses was simulated at C5–C6 on the basis of a validated finite element cervical model (C3–C7). The prostheses included ball-in-socket design with a fixed RC located on the inferior endplate (BS-FI) and on the superior endplate (BS-FS), with a mobile RC at the inferior endplate (BS-MI), dual articulation with a mobile RC between the endplates (DA-M), and sliding articulation with various RCs (SA-V). The spinal motions in flexion and extension served as a displacement loading at the C3 vertebrae. Results. Total disc replacements reduced extension moment. The ball-in-socket designs required less flexion moment, whereas the flexion stiffness of the spines with DA-M and SA-V was similar to that of the healthy model. The contributions of the implanted level to the global motions increased in the total disc replacements, except in the SA-V and DA-M models (in flexion). Ball-in-socket designs produced severe stress distributions in facet cartilage, whereas DA-M and SA-V produced more severe stress distribution on the bone-implant interface. Conclusion. Cervical stability was extremely affected in extension and partially affected in flexion by total disc replacement. With the prostheses with mobile RC, cervical curvature was readjusted under a low follower load. The SA-V and BS-FS designs exhibited better performances in the entire segmental stiffness and in the stability of the operative level than the BS-MI and BS-FI designs in flexion. The 5 designs demonstrated varying advantages relative to the stress distribution in the facet cartilages and on the bone-implant interface. Level of Evidence: 5